A Yoga for Liberation: Ramanuja’s Approach - Francis Vadakethala (Journal of Dharma, 1977)
According to Ramanuja, and the Indian way of thinking in general, the association of the individual self with the body is considered to be a bondage. It is a bondage because it restricts the freedom of the self which is essentially spiritual and God- like. By itself the individual self is capable of participating in the divine bliss; but because of the body which is of material nature (prakrti), it becomes attached to matter and to the pleasures and pains arising from the material nature. Body is, thus, the bondage of the self. Though essentially eternal and blissful, existentially the individual self is in bondage.